THE EFFECT OF PSYCHOEDUCATIONAL VIDEOS AND RELAXATION TECHNIQUES ON STRESS REDUCTION IN PREGNANT WOMEN AT THE PRATAMA LARASATI CLINIC IN 2025 - Amelia, Childa; Febriyani, Putri Agus; Ramadhan, Fenny Valianda Amelia; BR Ginting, Agus Santi; Wati, Wati; Amelia, Yuni Nur; Fitriyana, Fitriyana; Yulianingsih, Muliana (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Stress is a common psychological problem experienced by pregnant women and can have negative impacts on maternal health as well as fetal development. Unmanaged stress may increase the risk of pregnancy complications, emotional disturbances, and even preterm birth. This study aimed to analyze the effect of psychoeducational videos and relaxation techniques on reducing stress levels among pregnant women at Pratama Larasati Clinic in 2025.Methods: This research employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of first- to third-trimester pregnant women who met the inclusion criteria, selected through purposive sampling. The research instrument used a validated and reliable pregnancy stress scale questionnaire. The intervention group received psychoeducational videos about healthy pregnancy along with guided relaxation techniques delivered in several sessions, while the control group only received standard antenatal care. Data were analyzed using paired t- tests to examine within-group differences and independent t-tests to compare between groups. Results: The findings revealed a significant reduction in stress scores among pregnant women after receiving psychoeducational video and relaxation interventions (p= 0.03 < 0.05). In contrast, the control group showed no significant changes. Moreover, the difference in mean stress scores between the intervention and control groups was statistically significant, indicating the effectiveness of the intervention. Conclusion: The combination of psychoeducational videos and relaxation techniques was proven effective in reducing stress levels in pregnant women. This approach offers a simple, practical, and non-pharmacological alternative that can be integrated into antenatal care services. Its implementation should be considered by healthcare providers to improve maternal mental health during pregnancy